2015
DOI: 10.17660/actahortic.2015.1065.42
|View full text |Cite
|
Sign up to set email alerts
|

Dwarfing Rootstocks for 'Valencia' Sweet Orange

Abstract: The Brazilian and other citrus industries will likely require, among other technologies, the use of rootstocks that are suitable for higher planting densities with high production efficiency of high quality fruits and tolerant to abiotic and biotic stresses. Considering this approach, hybrid rootstocks have been obtained by the Citrus Breeding Program of Embrapa Cassava & Fruits, in Cruz das Almas, Bahia State, Brazil. One experiment evaluating the first three commercial crops of 'Valencia' sweet orange budded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The good performances of the rootstocks LVK x LCR-038, the 'Indio' citrandarin, and the 'Santa Cruz' Rangpur lime were also observed for 'Valência' sweet oranges under dry conditions in the Cerrado ecosystem, in the municipality of Colômbia, in the north of São Paulo state (Ramos et al, 2015). The rootstock influences the stability of production, production per plant, and accumulated production (Chaparro-Zambrano et al, 2015).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The good performances of the rootstocks LVK x LCR-038, the 'Indio' citrandarin, and the 'Santa Cruz' Rangpur lime were also observed for 'Valência' sweet oranges under dry conditions in the Cerrado ecosystem, in the municipality of Colômbia, in the north of São Paulo state (Ramos et al, 2015). The rootstock influences the stability of production, production per plant, and accumulated production (Chaparro-Zambrano et al, 2015).…”
Section: Resultsmentioning
confidence: 76%
“…These results are similar to those by França et al (2016), who verified that the rootstocks did not show any influence in relation to the dry grades, after evaluating 'Valencia Tuxpan' grafted onto 14 rootstocks, in Rio Real, Bahia state, Brazil. According to Ramos et al (2015), it is necessary to highlight the increasing importance of rational water consumption, which shows the need to develop drought-tolerant varieties, or to be more efficient in the use of available water. In this sense, Soares et al (2015) state that genotypes which exhibit superior water-tolerance behavior should be included in breeding programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Carvalho et al (2016b) observed that rootstocks common 'Rangpur' lime, 'Cravo Santa Cruz Rangpur' lime, 'Red Rough' lemon, 'Indio' and 'San Diego' citrandarins, as well as the hybrids TSKC x CTSW -058, TSKFL x CTARG -028, TSKC x (LCR x TR) -059, TSKC x CTARG -044 and TSKC x LHA -006, enabled the 'Pera CNPMF-D6' sweet orange, to lose little water by evapotranspiration and show high production efficiency in conditions of natural water deficit. In dry farming in Colômbia, SP, Brazil, Ramos et al (2015) found that 'Valência' sweet orange grafted on 'Indio' and 'Riverside' citrandarins had high production and vigor, even though their leaves showed symptoms of wrinkling as the result of drought in the region. Water deficit leads to decrease in photosynthesis rates by means of both stomatal and non-stomatal limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Higher concentrations of roots (RLD, TRL, diameter classes, and SRL) were found for the longitudinal profile, when compared to the orthogonal profile. This was probably due to the contribution of the root system of both rootstocks, because of the denser planting spacing, which has been a tendency for citriculture (Azevedo et al, 2015;Ramos et al, 2015). In addition, the area was more shaded, without machinery traffic and soil turning, with higher moisture (Souza et al, 2007) due to the low soil water evaporation potential, and had lower weed competition and higher soil fertilizer concentrations, contributing to a higher root concentration under the canopy projection.…”
Section: Resultsmentioning
confidence: 99%